QOLP-12. ILLNESS UNDERSTANDING AND PERCEPTIONS ABOUT PROGNOSIS IN PATIENTS WITH MALIGNANT GLIOMAS AND THEIR CAREGIVERS. (12th November 2021) - Rhee, John; Mesa, Michelle; Kaslow-Zieve, Emilia; Traeger, Lara; El-Jawahri, Areej; Temel, Jennifer; Forst, Deborah
Abstract: BACKGROUND: Malignant gliomas (MG) are incurable tumors with limited survival. Prognostic awareness is essential for informed decision making, but patients' and caregivers' perceptions about their illness and prognosis are not well understood. METHODS: We conducted a prospective, single-institution study in patients with newly diagnosed MG and their caregivers, following the outpatient visit in which their neuro-oncologist disclosed pathology results and discussed treatment options. Participants (patients and caregivers) completed the Prognosis and Treatment Perceptions Questionnaire to assess information preferences, treatment goals and prognostic understanding. RESULTS: Of patients approached, 82% (14/17) were eligible and enrolled in the study. The majority of patients were male (9/14, 64%), median age 60 years (range 26-76) and had a glioblastoma (11/14, 79%). Most caregivers were female (8/11, 73%) and married to the patient (7/11, 64%). The majority of patients said their cancer was curable (10/13, 77%, one patient did not answer), while only 3/11 caregivers (27%) said the patient's cancer was curable. Furthermore, 7/13 patients (54%) and 8/11 caregivers (73%) reported that their oncologist said their cancer was not curable, and the remainder (6/13 patients, 46% and 3/11 caregivers, 27%) said the oncologist "did not say" whether it was curable. Most patients (10/14, 71%) and caregivers (8/11, 73%) expressed a tendency to focus on the best-case scenario in response to information from their oncology team about their cancer. CONCLUSION: Although most patients with MG and their caregivers acknowledged being told that their cancer was incurable, the majority of patients reported that their cancer was curable. Patients and caregivers often reported focusing on the best-case scenario regarding their cancer. Further investigation is warranted to explore strategies to support patients and caregivers learning about their incurable cancer.